2015
DOI: 10.1038/ismej.2015.81
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic resolution of microbial functions in deep-sea hydrothermal plumes across the Eastern Lau Spreading Center

Abstract: Microbial processes within deep-sea hydrothermal plumes affect ocean biogeochemistry on global scales. In rising hydrothermal plumes, a combination of microbial metabolism and particle formation processes initiate the transformation of reduced chemicals like hydrogen sulfide, hydrogen, methane, iron, manganese and ammonia that are abundant in hydrothermal vent fluids. Despite the biogeochemical importance of this rising portion of plumes, it is understudied in comparison to neutrally buoyant plumes. Here we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 87 publications
(124 reference statements)
10
109
1
2
Order By: Relevance
“…U copiosus genome is ∌94% complete, based on domain-specific single-copy housekeeping genes commonly used to estimate genome completion 23 (Supplementary Table 3). This list of single-copy genes has been used to estimate genome completeness in several recent studies 13,63 . When we analysed the genome using another metric of genome completeness (checkM 64 ), the results suggested that the genome was 80% complete with 4% contamination, a level categorized as a 'substantially complete draft with low contamination'.…”
Section: Methodsmentioning
confidence: 99%
“…U copiosus genome is ∌94% complete, based on domain-specific single-copy housekeeping genes commonly used to estimate genome completion 23 (Supplementary Table 3). This list of single-copy genes has been used to estimate genome completeness in several recent studies 13,63 . When we analysed the genome using another metric of genome completeness (checkM 64 ), the results suggested that the genome was 80% complete with 4% contamination, a level categorized as a 'substantially complete draft with low contamination'.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a study within a single vent field at Axial Seamount showed differences in gene expression patterns between both diffuse vents as well as within the intra‐field waters between vent sites (Olins et al ., ). Finally, through the reconstruction of genomes from metagenomes (Tyson et al ., ; Dick et al ., ; Hug et al ., ), recent genomic binning studies at hydrothermal systems have revealed the presence of novel microbial and viral groups as well as their metabolic potential, including the discovery of auxiliary metabolic genes for sulfur oxidation within deep ocean viruses and the potential importance of hydrocarbon degradation distal to venting fluids, including within hydrothermal plumes (Anantharaman et al ., ; Li et al ., ; Sheik et al ., ; Meier et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…This process is consistent with experimental evidence and theoretical models indicating that viral lysis can enhance carbon cycling and nutrient regeneration within the microbial loop (Middelboe et al ., ; Poorvin et al ., ; Weinbauer et al ., ; Shelford et al ., ; Weitz et al ., ). Recent studies suggest a tight coupling between chemoautotrophic and HCP in deep‐sea hydrothermal vent ecosystems (Bennett et al ., ), and viruses infecting the dominant chemoautotrophs have been inferred as a possible link between primary and secondary production processes in such systems (Anantharaman et al ., 2014, 2016; Li et al ., ). To our knowledge, we present here the first experimental evidence supporting the hypothesis that provirus‐host interactions can profoundly influence the carbon cycling in hydrothermal vents, opening novel research perspectives on these dynamics.…”
Section: Discussionmentioning
confidence: 97%